ESTIMATION OF TOXIC EFFECTS OF MEDICINAL PREPARATION OF CABAZITAXEL - O. I. Avdeeva; E. V. Shekunova; A. A. Muzhikyan; M. N. Makarova; V. G. Makarov; A. Ya. Hymenov (Разработка и регистрация лекарственных средств)
A study of the toxic properties of the drug cabazitaxel was carried out on outbred rats with intravenous administration. The toxicity was assessed with a single and repeated weekly administration of the drug. It was noted that the toxic and lethal effects were delayed. In an acute experiment, the mean lethal dose was calculated, which for animals of both sexes was 4.2 mg/kg. With repeated administration, the maximum tolerated dose was 1.5 mg/kg, lethal - 2.5 mg/kg. The clinical picture of intoxication was characterized by depressed behavior, decreased response to external stimuli and tonus of skeletal muscles, tachypnea and diarrhea. A decrease in feed intake and body weight of animals was detected. Target organs of toxic effect of cabazitaxel: gastrointestinal tract, liver, bone marrow, reproductive system of male rats.